Studying the possibilities of pharmacological correction of hypoxia-induced pulmonary hypertension using a phenolic compound with a laboratory cypher KUD975 - L. V. Korokina (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2024)
The aim of our work was to study a pharmacological activity of a selective arginase-2 and thrombin inhibitor from a phenolic compounds group with a laboratory cypher KUD975 on a model of arterial pulmonary hypertension induced by hypoxia.Materials and methods. To simulate pulmonary hypertension (РН), animals were placed in a normobaric hypoxic chamber and subjected to 5 weeks of hypoxia with an oxygen content of 10% in the air. After 3 weeks of hypoxia, the animals were administered with the test compound KUD975 (intragastrically, at a dose of 2 mg/kg once a day for 2 weeks). L-norvaline (intragastrically, 20 mg/kg) was used as a reference drug. To assess the development and correction of РН, measurements of cardiohemodynamics, analysis of blood gas composition, study of the number of circulating endothelial precursor cells (EPCs), quantitative PCR assessing the expression of mRNA VEGF-R2, SGF-1 (stromal growth factor-1) and MCP-1 (monocyte chemoattractant protein-1). Next, a histological examination of the lungs and heart was performed, the degree of pulmonary edema and the concentration of cardiotrophin-1 and atrial natriuretic peptide were assessed.Results. The administration of the studied phenolic compound with laboratory cypher KUD975, as well as the reference drug L-norvaline, led to a decrease in the right ventricular systolic pressure against the background of modeling РН. The present study shows a more than twice-fold decrease in the number of circulating (EPCs) in the animals group with modeling a hypoxia-induced circulatory РН (171.3±12.1) in comparison with the group of intact animals (296.1±31.7; p=0.0018). The recovery of EPCs was noted in the animals group administered with KUD-975 and L-norvaline, up to 247.5±34.2 (p=0.0009 compared with a pulmonary arterial hypertension (PAH) and 235.6±36.4 (p=0.008 compared to PAH), respectively. The studied compounds had a protective effect by statistically significantly increasing the expression of VEGF-R2 mRNA and decreasing the expression of SGF-1 mRNA, reducing the lung moisture coefficient and the concentrations of cardiotrophin-1 and atrial natriuretic peptide and preventing vascular remodeling caused by hypoxia.Conclusion. When studying the pharmacological activity, it was shown that the phenolic compound with the laboratory cypher KUD975 normalizes hemodynamic parameters, reduces the signs of remodeling of the heart and pulmonary vessels and has a pronounced endothelial protective effect on the model of hypoxia-induced РН, and is superior to the activity of the reference drug L-norvaline.